Teaching reading to the educable mentally retarded children (primary level) - Inciong, Teresita Grafilo 1943- (College of Education, University of the Philippines Diliman, 1969)
This paper aimed to find out the activities and experiences that should be included in an effective program to suit the needs of the educable mentally retarded primary level. The researcher used books, magazines, and journals that contain materials about teaching reading to the educable mentally retarded. The author took into consideration some of the factors which affect the reading program of the educable mentally retarded. The study pointed out the necessity to extend and prolong the various reading periods for EMR. Since many repetitions must be given to the mentally retarded child, greater varieties of presentation must be made.